13C‐MFA delineates the photomixotrophic metabolism of Synechocystis sp. PCC 6803 under light‐ and carbon‐sufficient conditions. Issue 5 (16th April 2014) - You, Le; Berla, Bert; He, Lian; Pakrasi, Himadri B.; Tang, Yinjie J.
Abstract The central carbon metabolism of cyanobacteria is under debate. For over 50 years, the lack of α‐ketoglutarate dehydrogenase has led to the belief that cyanobacteria have an incomplete TCA cycle. Recent in vitro enzymatic experiments suggest that this cycle may in fact be closed. The current study employed 13C isotopomers to delineate pathways in the cyanobacterium Synechocystis sp. PCC 6803. By tracing the incorporation of supplemented glutamate into the downstream metabolites in the TCA cycle, we observed a direct in vivo transformation of α‐ketoglutarate to succinate. Additionally, isotopic tracing of glyoxylate did not show a functional glyoxylate shunt and glyoxylate was used for glycine synthesis. The photomixotrophic carbon metabolism was then profiled with 13C‐MFA under light and carbon‐sufficient conditions. We observed that: (i) the in vivo flux through the TCA cycle reactions (α‐ketoglutarate → succinate) was minimal (<2%); (ii) the flux ratio of CO2 fixation was six times higher than that of glucose utilization; (iii) the relative flux through the oxidative pentose phosphate pathway was low (<2%); (iv) high flux through malic enzyme served as a main route for pyruvate synthesis. Our results improve the understanding of the versatile metabolism in cyanobacteria and shed light on their application for photo‐biorefineries.